A joint analysis of AMI and CARMA observations of the recently discovered SZ galaxy cluster system AMI-CL J0300+2613 - Shimwell, T.; Carpenter, J.; Feroz, F.; Grainge, K.; Hobson, M.; Hurley-Walker, Natasha; Lasenby, A.; Olamaie, M.; Perrott, Y.; Pooley, G.; Rodriguez-Gonzalvez, C.; Rumsey, C.; et al. (Oxford University Press, 2013)
Saunders